Comparative study of outcome of Postdated Pregnancy of Primaegravida and Multigravida Patients (Journal of Dhaka National Medical College & Hospital, 2014)
Background : Postdated pregnancy is a high risk pregnancy in obstetric situation because the perinatal morbidity and mortality exceed that of term pregnancies. According to the definition provided by the WHO and International Federations of Obstetrics and Gynaecology, a prolonged pregnancy is one that exceeds 294 days or 42 weeks from the  first day of last menstrual period and postdated pregnancy is a condition which has passed beyond the expected date of delivery. Objectives:To reduce the maternal and perinatal morbidity and mortality and to reduce the incidence of operative delivery in primigravida and multigravida patients in post dated pregnancy.Materials and methods :The study was carried out from January to June, 2012 in the department of Obstetrics and   Gynaecology, Dhaka National Medical Institute Hospital (DNMIH) Dhaka. Out of 206 women with postdated pregnancy, admitted during the study period in the obstetric ward of DNMIH, 80 women who fulfilled inclusion criteria, constituted the study population.Results :In the present study out of 80 women with postdated pregnancy, 42(52.5%) were primaegravida and 38(47.5%) were multigravida. All the women of primaegravida group belonged to age group